Ground- and Excited-State Quinones: Perspectives in Organocatalysis and Visible-Light Photocatalysis - Lerch, Stephanie; Unkel, Lisa-Natascha; Wienefeld, Patrick; Brasholz, Malte (Synlett, 2014)
Quinone organocatalysis is an emerging area, and this report highlights some recently developed thermal and photocatalytic reactions, with particular emphasis on photooxygenation reactions. Further, it is discussed how the orthogonal ground- and excited-state reactivities of quinones can be utilized for the development of tandem catalytic processes.
Keywords: quinones; organocatalysis; photochemistry; photooxidations; tandem reactions